The Intersections of the Economic and Cultural in U.S. Labor's Pro-Migrant Politics - Basok, Tanya (Social justice, 2008)
A study examined migrant rights activism by organized labor in the U.S. as a combination of economic goals and cultural expressions. Data were obtained from public statements on migrant workers rights in printed and electronic media between 2003 and 2006, made by labor activists and members of grass-roots organizations. Findings indicated that the memories of migration of those with leadership roles in unions, whether those memories are their own or have been shared by family members, constitute a framework of meaning that influences their views and attitudes toward present-day migrants and, as a result, the attitudes of the unions they work for. Findings suggested that identities shaped by memories of migration evoke empathy toward modern-day migrants and stimulate activism on their behalf. Findings are discussed in detail.